Degradation behavior of SiO2f/Al2O3-SiO2 composites: Anti-oxidation behavior and high-temperature flexural strength. Issue 5 (1st April 2019) - Jin, Wen; Lu, Yi; Si, Zhou; Yi, Wang; Yang, Xiang
Abstract: 2.5-Dimensional SiO2 fiber-reinforced Al2 O3 -SiO2 (SiO2f /Al2 O3 -SiO2 ) composites were prepared by the sol-gel method, using diphasic SiO2 sol as the precursor into which Al2 O3 powders were added. Their antioxidative behaviors and flexural strengths at high temperature were tested and compared. In an oxidation atmosphere, the composites showed high oxidation resistance, with a flexural strength retention ratio of over 90.00% at 1200 °C. After oxidation at 1500 °C, the mass retention ratio and flexural strength were 97.49% and 65.0 MPa respectively. The oxidation resistance of SiO2f /Al2 O3 -SiO2 composites was higher than that of SiO2f /SiO2 composites. After high-temperature test, the flexural strength retention ratios of SiO2f /SiO2 and SiO2f /Al2 O3 -SiO2 composites were 86.18% and 94.80% respectively, and the latter had a flexural strength of 134.9 MPa. SiO2 f /Al2 O3 -SiO2 composites worked better than SiO2f /SiO2 composites did in the flexural strength test at 1200 °C. The mechanical performance degradation and mass variations of the composites during tests were closely associated with their microstructural evolutions. Highlights: SiO2f /Al2 O3 -SiO2 composites had been fabricated by Sol-Gel method. The oxidation behavior of SiO2f /Al2 O3 -SiO2 composites were investigated and compared. High-temperature flexural property of SiO2f /Al2 O3 -SiO2 composites were investigated and compared. The degradation of mechanical property and mass variation were closely related to the evolution of micro-structural in the composites during the tests.